Modified high-nickel positive electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611142574.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-20
AI Technical Summary
但是随着镍含量的不断提高,其结构稳定性越来越差,进而影响锂离子二次电池的循环性能和存储性能
①采用阴阳离子 共掺杂调控晶粒生长与形貌+原位梯度共包覆优化策略,通过高价阳离子(Mo6-)与电负性较强的阴离子(F-)共掺杂协同实现调控晶粒生长与形貌,利用高价阳离子钉扎晶界、抑制一次颗粒过度长大并诱导径向排列,利用阴离子产生“电荷补偿效应”,抵消因离子半径差异导致的晶格畸变,获得形貌均一的单晶颗粒,体相与界面稳定性提升。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and more specifically, to a modified high-nickel cathode material, its preparation method, and its application. Background Technology
[0002] Due to the significant advancements in lithium-ion rechargeable batteries, higher demands have been placed on their energy density, cycle performance, and safety. High-nickel cathode active materials are considered the best choice to meet high energy density requirements. However, with the continuous increase in nickel content, their structural stability deteriorates, thereby affecting the cycle performance and storage performance of lithium-ion rechargeable batteries. Summary of the Invention
[0003] The purpose of this invention is to overcome the problems existing in the prior art and to provide a modified high-nickel cathode material, its preparation method, and its application.
[0004] The technical problem solved by this invention is achieved by the following technical solution.
[0005] The present invention provides a modified high-nickel cathode material, comprising a high-nickel cathode material matrix and a coating layer covering the surface of the high-nickel cathode material matrix, wherein the high-nickel cathode material matrix is doped with Mo and F, and the coating layer contains Zr and Ta.
[0006] The present invention provides a method for preparing the above-mentioned modified high-nickel cathode material, comprising: preparing a high-nickel cathode material matrix doped with Mo and F, and then coating the surface with a Zr-containing compound and a Ta-containing compound to obtain the modified high-nickel cathode material.
[0007] The present invention provides a secondary battery comprising the above-mentioned modified high-nickel ternary cathode material.
[0008] The present invention has the following beneficial effects: ① A strategy of co-doping of anions and cations to regulate grain growth and morphology, combined with in-situ gradient co-coating optimization, was adopted, using high-valence cations (Mo) 6- ) and the more electronegative anion (F - Co-doping synergistically achieves control over grain growth and morphology. High-valence cations pin grain boundaries, suppress excessive growth of primary particles and induce radial alignment. Anions generate a "charge compensation effect" to offset lattice distortion caused by differences in ionic radii, resulting in single-crystal particles with uniform morphology and improved bulk and interface stability.
[0009] ② By utilizing the residual alkali on the surface of high-nickel materials to generate Li2ZrO3 (resistant to high pressure and suppressing side reactions) and LiTaO3 (high ionic conductivity and compatible with sulfides) in situ, a dense composite interface layer is formed, which greatly improves the cycle performance and storage performance. Attached Figure Description
[0010] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0011] Figure 1 This is a scanning electron microscope image of the high-nickel cathode material substrate prepared in Example 1; Figure 2 This is a scanning electron microscope image of the high-nickel cathode material substrate prepared in Comparative Example 1. Detailed Implementation
[0012] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0013] The following is a detailed description of a modified high-nickel cathode material, its preparation method, and its application provided by embodiments of the present invention.
[0014] In a first aspect, the present invention provides a modified high-nickel cathode material, comprising a high-nickel cathode material matrix and a coating layer covering the surface of the high-nickel cathode material matrix, wherein the high-nickel cathode material matrix is doped with Mo and F, and the coating layer contains Zr and Ta.
[0015] In some alternative embodiments, the chemical formula of the high-nickel cathode material matrix is Li. a Ni b Co c Mn d M e O2, where 0.95≤a≤1.05, 0.8≤b≤0.1, 0≤c≤0.15, 0≤d≤0.15, 0.0002≤e≤0.05; Preferably, the high-nickel cathode material matrix has a single-crystal morphology. The doping amounts of Mo and F in the high-nickel cathode material matrix are 500-10000ppm and 500-10000ppm, respectively, and the ratio of Mo to F doping amounts is in the range of 0.7-1.0. If the doping amounts of Mo and F are too low, they cannot suppress the excessive growth of primary particles and induce radial alignment, which can easily lead to excessively large particle growth or uneven particle size. If the doping amounts are too high, the effect of suppressing primary particle growth is too strong, which can easily lead to insufficient particle growth and the formation of secondary spheres or quasi-single-crystal morphologies.
[0016] In some optional embodiments, the coating layer contains a Zr-containing compound and a Ta-containing compound, with the coating amounts of the Zr-containing compound and the Ta-containing compound being 500-10000 ppm and 500-10000 ppm, respectively. If the coating amounts of the Zr-containing compound and the Ta-containing compound are too low, the resulting coating layer will be thin or uneven, which may easily lead to direct contact between the material surface and the electrolyte, potentially causing serious side reactions and affecting the material's cycling performance. If the coating amounts are too high, the resulting coating layer will be too thick, which will also affect the capacity utilization. Preferably, the coating layer is a co-coating layer of Li2ZrO3 and LiTaO3.
[0017] In some alternative embodiments, the particle size of the high-nickel cathode material matrix is 0.5-4 μm, and the thickness of the coating layer is 3-30 nm.
[0018] Secondly, the present invention provides a method for preparing the above-mentioned modified high-nickel cathode material, comprising: preparing a high-nickel cathode material matrix doped with Mo and F, and then coating its surface with a Zr-containing compound and a Ta-containing compound to obtain the modified high-nickel cathode material.
[0019] In some optional embodiments, the following steps are included: mixing a high-nickel ternary precursor with a lithium source, a molybdenum source, and a fluorine source, and then sintering it once without washing with water. The sintered material is directly placed in a solution containing a zirconium source and a tantalum source and stirred. After drying, it is sintered a second time to obtain a modified high-nickel cathode material.
[0020] In some optional embodiments, the preparation of the primary sintering material includes: mixing a high-nickel ternary precursor with a lithium source, a molybdenum source, and a fluorine source, and then performing a primary sintering under an oxygen-containing atmosphere to prepare the primary sintering material. Preferably, the primary sintering temperature is 700-1000℃ and the sintering time is 6-20h. If the primary sintering temperature is too low, the particles cannot grow sufficiently and the morphology may become secondary spheres or single crystals. If the temperature is too high, the particles will grow too large and affect the material capacity.
[0021] In some optional embodiments, the preparation of the modified high-nickel cathode material includes: placing the primary sintered material obtained by primary sintering in a solution containing zirconium source and tantalum source and stirring it; after evaporation to remove the solvent and vacuum drying, performing secondary sintering to obtain the modified high-nickel cathode material. Preferably, the evaporation temperature is 50-90℃, the secondary sintering temperature is 500-800℃, and the sintering time is 6-20h. If the secondary sintering temperature is too low, it will affect the reaction between zirconium, tantalum and residual alkali on the surface of the primary sintering material. If the temperature is too high, it may cause secondary growth of material particles, affecting performance.
[0022] In some alternative embodiments, the high-nickel ternary precursor is composed of Ni x Co y Mn (1-x-y) (OH)2, wherein 0.5≤x<0.95, 0≤y≤0.5, the lithium source includes at least one of lithium hydroxide and lithium carbonate, the molybdenum source includes at least one of molybdenum oxide and molybdenum sulfide, the fluorine source includes at least one of hydrofluoric acid and sodium fluoride, the zirconium source includes at least one of zirconium propoxide, tetrabutyl zirconate and zirconium acetate, and the tantalum source includes at least one of tantalum ethoxide, tantalum butoxide and tantalum methoxide.
[0023] Thirdly, the present invention provides a secondary battery, including the aforementioned modified high-nickel cathode material.
[0024] The present invention will be further described below with reference to embodiments.
[0025] Example 1 3kg of Ni 90 Co6Mn4(OH)2 ternary precursor was mixed with 1.4 kg lithium hydroxide, 4.5 g molybdenum oxide and 7.9 g sodium fluoride using a high-speed mixing method for 40 min. After uniform mixing, the mixture was sintered in two stages at 500℃ for 3 h and 850℃ for 10 h to obtain high-nickel single crystal material.
[0026] The residual lithium Li2CO3 on the surface of the above single crystal is not removed by water washing, but is directly used as the lithium source for in-situ reaction. It is mixed with a mixed solution of 0.05% zirconium isopropoxide and 0.05% tantalum ethoxide at a solid-liquid ratio of 1:3, sonicated for 30 min, stirred and evaporated in a water bath at 80°C, vacuum dried, and then sintered in oxygen at 550°C for 4 h to produce a double in-situ reaction and generate a co-coating layer.
[0027] Use solid-state batteries to evaluate capacity, rate capability, and cycle life.
[0028] Example 2 3kg of Ni 90 Co6Mn4(OH)2 ternary precursor was mixed with 1.4 kg lithium hydroxide, 9.0 g molybdenum oxide and 15.8 g sodium fluoride using a high-speed mixing method for 40 min. After uniform mixing, the mixture was sintered in two stages at 500℃ for 3 h and 850℃ for 10 h to obtain high-nickel single crystal material.
[0029] The residual lithium Li2CO3 on the surface of the above single crystal is not removed by water washing, but is directly used as the lithium source for in-situ reaction. It is mixed with a mixed solution of 0.05% zirconium isopropoxide and 0.05% tantalum ethoxide at a solid-liquid ratio of 1:3, sonicated for 30 min, stirred and evaporated in a water bath at 80°C, vacuum dried, and then sintered in oxygen at 550°C for 4 h to produce a double in-situ reaction and generate a co-coating layer.
[0030] Use solid-state batteries to evaluate capacity, rate capability, and cycle life.
[0031] Example 3 3kg of Ni 90 Co6Mn4(OH)2 ternary precursor was mixed with 1.4 kg lithium hydroxide, 4.5 g molybdenum oxide and 7.9 g sodium fluoride using a high-speed mixing method for 40 min. After uniform mixing, the mixture was sintered in two stages at 500℃ for 3 h and 850℃ for 10 h to obtain high-nickel single crystal material.
[0032] The residual lithium Li2CO3 on the surface of the above single crystal was not removed by water washing, but was directly used as the lithium source for in-situ reaction. It was mixed with a mixed solution of 0.1% zirconium isopropoxide and 0.1% tantalum ethoxide at a solid-liquid ratio of 1:3, sonicated for 30 min, and the solvent was evaporated by stirring in an 80°C water bath. After vacuum drying, it was sintered in oxygen at 550°C for 4 h to produce a double in-situ reaction and generate a co-coating layer.
[0033] Use solid-state batteries to evaluate capacity, rate capability, and cycle life.
[0034] Comparative Example 1 The steps are similar to those in Example 1, except that molybdenum oxide and sodium fluoride are not added during the preparation process.
[0035] Comparative Example 2 The steps are similar to those in Example 1, except that 45g of molybdenum oxide and 79g of sodium fluoride are added during the preparation process.
[0036] Comparative Example 3 The steps are similar to those in Example 1, except that 4.5g of niobium oxide and 7.9g of sodium fluoride are added during the preparation process.
[0037] Comparative Example 4 Similar to the steps in Example 1, except that zirconium isopropoxide and tantalum ethoxide are not added during the preparation process.
[0038] Comparative Example 5 The steps are similar to those in Example 1, except that 1% zirconium propoxide and 1% tantalum ethanol are added during the preparation process.
[0039] Comparative Example 6 The steps are similar to those in Example 1, except that 0.05% magnesium acetate and 0.05% tantalum ethoxide are added during the preparation process.
[0040] Solid-state electrochemical performance testing of cathode materials: The cathode materials prepared in the examples and comparative examples were assembled according to the following method: In a glove box, 100 mg of Li6PS5Cl solid electrolyte powder was evenly sprinkled into a tableting mold and pressed for 50 s at 400 MPa to form a tablet. Then, 10 mg of a uniformly mixed composite cathode material (composed of cathode material: conductive agent acetylene black: Li6PS5Cl = 90:5:5) was evenly sprinkled on one side of the solid electrolyte tablet and pressed for 100 s at 200 MPa. Finally, a 30 μm thick lithium metal sheet was added to the side of the sulfide solid electrolyte and pressed for 50 s at 200 MPa to obtain an all-solid-state battery.
[0041] The electrochemical performance of the all-solid-state battery was tested on the Blue Electric System. The test voltage range was 1.9-3.7V, the clamping pressure was 80MPa, and the test temperature was 25℃. The results are shown in Table 1.
[0042] Table 1
[0043] Combining the above table 1 and Figure 1-2 It can be seen that: compared with the high-nickel cathode material substrate prepared in Comparative Example 1 (see...) Figure 2 The high-nickel cathode material substrate prepared in Example 1 effectively suppressed excessive primary particle growth through molybdenum and fluorine doping, resulting in single-crystal particles with relatively uniform morphology (see Example 1). Figure 1 As can be seen from Examples 1, 2, and 3 in Table 1, appropriately increasing the amount of molybdenum and fluorine additives improves both rate capability and cycle life to a certain extent, while appropriately increasing the amount of zirconium and tantalum additives slightly decreases capacity but improves cycle life to a certain extent. From Comparative Examples 1, 2, and 3, it can be seen that after excessive doping with molybdenum and fluorine additives, the capacity and cycle life of the solid-state battery are severely reduced. Changing the additives to niobium and fluorine significantly improves capacity and cycle life compared to no doping, but the effect is not as good as co-doping with molybdenum and fluorine additives. From Comparative Examples 4, 5, and 6, it can be seen that after coating with excessive zirconium and tantalum additives, the capacity and cycle life of the solid-state battery are severely reduced. Changing the additives to magnesium and tantalum slightly reduces capacity and improves cycle life to a certain extent, but the effect is not as good as co-coating with zirconium and tantalum additives. Therefore, the modified high-nickel cathode material provided by this invention, through synergistic modification from both bulk doping and surface coating aspects, produces a ternary single-crystal cathode material with good stability, significantly improving battery capacity, rate capability, and cycle life.
[0044] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A modified high-nickel cathode material, characterized in that, It includes a high-nickel cathode material matrix and a coating layer covering the surface of the high-nickel cathode material matrix. The high-nickel cathode material matrix is doped with Mo and F, and the coating layer contains Zr and Ta.
2. The modified high-nickel cathode material according to claim 1, characterized in that, The chemical formula of the high-nickel cathode material matrix is Li a Ni b Co c Mn d M e O2, where 0.95≤a≤1.05, 0.8≤b≤0.1, 0≤c≤0.15, 0≤d≤0.15, 0.0002≤e≤0.05, and M represents Mo and F; Preferably, the high-nickel cathode material matrix has a single-crystal morphology, and the doping amounts of Mo and F in the high-nickel cathode material matrix are 500-10000ppm and 500-10000ppm, respectively, and the ratio of the doping amounts of Mo and F is in the range of 0.7-1.
0.
3. The modified high-nickel cathode material according to claim 1, characterized in that, The coating layer contains a Zr-containing compound and a Ta-containing compound, wherein the coating amounts of the Zr-containing compound and the Ta-containing compound are 500-10000 ppm and 500-10000 ppm, respectively. Preferably, the coating layer is a co-coating layer of Li2ZrO3 and LiTaO3.
4. The modified high-nickel cathode material according to any one of claims 1-3, characterized in that, The high-nickel cathode material matrix has a particle size of 0.5-4 μm, and the coating layer has a thickness of 3-30 nm.
5. A method for preparing a modified high-nickel cathode material according to any one of claims 1-4, characterized in that, include: A high-nickel cathode material matrix doped with Mo and F was prepared, and then a Zr-containing compound and a Ta-containing compound were coated on its surface to prepare a modified high-nickel cathode material.
6. The preparation method according to claim 5, characterized in that, Includes the following steps: The high-nickel ternary precursor is mixed with lithium, molybdenum and fluorine sources and then sintered once. No water washing is required. The first sintered material is directly placed in a mixture containing zirconium and tantalum sources and stirred. After drying, it is sintered a second time to obtain the modified high-nickel cathode material.
7. The preparation method according to claim 6, characterized in that, The preparation of the primary sintering material includes: mixing a high-nickel ternary precursor with a lithium source, a molybdenum source, and a fluorine source, and then performing a primary sintering under an oxygen-containing atmosphere to prepare the primary sintering material. Preferably, the sintering temperature is 700-1000℃ and the time is 6-20h.
8. The preparation method according to claim 6, characterized in that, The preparation of the modified high-nickel cathode material includes: placing the primary sintered material obtained by primary sintering into a solution containing zirconium source and tantalum source and stirring it; after evaporation to remove the solvent and vacuum drying, a secondary sintering is performed to obtain the modified high-nickel cathode material. Preferably, the evaporation temperature is 50-90℃, the secondary sintering temperature is 500-800℃, and the time is 6-20h.
9. The preparation method according to claim 6, characterized in that, The high-nickel ternary precursor is composed of Ni x Co y Mn (1-x-y) (OH)2, wherein 0.5≤x<0.95, 0≤y≤0.5, the lithium source includes at least one of lithium hydroxide and lithium carbonate, the molybdenum source includes at least one of molybdenum oxide and molybdenum sulfide, the fluorine source includes at least one of hydrofluoric acid and sodium fluoride, the zirconium source includes at least one of zirconium propoxide, tetrabutyl zirconate and zirconium acetate, and the tantalum source includes at least one of tantalum ethoxide, tantalum butoxide and tantalum methoxide.
10. A secondary battery, characterized in that, This includes the modified high-nickel ternary cathode material according to any one of claims 1-4 or the modified high-nickel ternary cathode material prepared by the preparation method according to any one of claims 5-9.